2013
DOI: 10.1038/emboj.2013.146
|View full text |Cite
|
Sign up to set email alerts
|

Bace1 and Neuregulin-1 cooperate to control formation and maintenance of muscle spindles

Abstract: The protease β-secretase 1 (Bace1) was identified through its critical role in production of amyloid-β peptides (Aβ), the major component of amyloid plaques in Alzheimer's disease. Bace1 is considered a promising target for the treatment of this pathology, but processes additional substrates, among them Neuregulin-1 (Nrg1). Our biochemical analysis indicates that Bace1 processes the Ig-containing β1 Nrg1 (IgNrg1β1) isoform. We find that a graded reduction in IgNrg1 signal strength in vivo results in increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
142
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(144 citation statements)
references
References 73 publications
2
142
0
Order By: Relevance
“…Thus, Bace1 mutant mice and zebrafish display deficits in developmental myelination. In addition, remyelination of peripheral nerves and formation and maintenance of muscle spindles are impaired in mice, and these phenotypes resemble the well-characterized ones observed when Nrg1/ErbB signaling is ablated (Hu et al, 2006;Willem et al, 2006;Cheret et al, 2013;Fleck et al, 2013). It should be noted that phenotypes in Bace1 mutants are not as strong as the ones observed in Nrg1 signaling mutants, indicating that other proteases participate in shedding.…”
Section: Proteolytic Processing Is Rate Limiting For Nrg1 Activity Anmentioning
confidence: 63%
See 2 more Smart Citations
“…Thus, Bace1 mutant mice and zebrafish display deficits in developmental myelination. In addition, remyelination of peripheral nerves and formation and maintenance of muscle spindles are impaired in mice, and these phenotypes resemble the well-characterized ones observed when Nrg1/ErbB signaling is ablated (Hu et al, 2006;Willem et al, 2006;Cheret et al, 2013;Fleck et al, 2013). It should be noted that phenotypes in Bace1 mutants are not as strong as the ones observed in Nrg1 signaling mutants, indicating that other proteases participate in shedding.…”
Section: Proteolytic Processing Is Rate Limiting For Nrg1 Activity Anmentioning
confidence: 63%
“…It should be noted that phenotypes in Bace1 mutants are not as strong as the ones observed in Nrg1 signaling mutants, indicating that other proteases participate in shedding. However, overexpression of type I Nrg1 in transgenic mice induces supernumerary muscle spindles in a strictly Bace1-dependent manner, indicating that this isoform requires Bace1 processing for its function (Cheret et al, 2013). The finding that Bace1 cleaves Nrg1 might be of interest for new therapies that are being developed for Alzheimer's disease.…”
Section: Proteolytic Processing Is Rate Limiting For Nrg1 Activity Anmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting, however, that, as a consequence of the unprocessed BACE1 substrate neuregulin 1, BACE1-deficient mice also show muscle spindle defects and reduced myelination of peripheral nerves, which also give rise to impaired motor coordination. 68 Thus, the contributions of cerebellar dysfunction and peripheral deficits to the motor symptoms of BACE1 ¡/¡ mice remain to be determined in future studies.…”
Section: Bace1 and Neuronal Na V Channelsmentioning
confidence: 99%
“…Nrg1 increases terminal Schwann cells survival after postnatal denervation and promotes process extension required for new NMJ formation (Trachtenberg and Thompson, 1996;Hayworth et al, 2006). It has been also shown that Nrg1 alterations produce severe deficits in the formation and maturation of muscle spindles, thereby compromising the proprioceptive sensory system (Cheret et al, 2013). The exact role of Nrg1 type I (thereafter named Nrg1-I) on the peripheral nervous system is not fully known.…”
Section: Introductionmentioning
confidence: 99%